Core Competencies needed for performing effective digital teaching by medical teachers - Muhammad Saaiq; Rehan Ahmed Khan; Rahila Yasmeen (Mashhad University of Medical Sciences, 2023)
Background: The digital teaching is quite different from the traditional in-person classroom teaching. The purpose of the thematic review was to identify the development and future prospects of digital teaching with reference to medical and dental teachers as well as to identify any published competency frameworks in this regard.Method: The authors conducted a thematic review of the relevant literature published between1994-2022. The databases searched included PubMed, Education Resources Information Center (ERIC), and Google Scholar. Manual search was also carried out so as not to miss any relevant published literature.Results: The initial search yielded 31,389 publications. At the search phase, the identification of publications was based on the titles of the publications. At the screening phase, 31,322 records were excluded because of their being irrelevant or duplicated. The remaining 67 articles were further screened by reading the abstracts. Out of these 67 publications, 24 were excluded because of being non-relevant. At the appraisal phase, 43 publications were assessed for eligibility. At final synthesis phase of the literature review, 26 publications were included.Conclusion: The available published literature on digital teaching was focused predominantly on primary and secondary school students. The digital competency frameworks were designed for the transfer of the knowledge component and dealt mostly with children. These frameworks did not meet the specific requirements of medical teachers. The latter have to transfer not only the knowledge domain, but also teach clinical skills and professional attitudes to their adult learners. Hence, they need a framework which should provide for these added competencies and real-life, patient-oriented clinical scenarios.